Surgery for maxillary oral squamous cell carcinoma: the effect of surgical resection margins and elective neck dissection on oncological outcomes. Issue 3 (March 2023) - Woo, S.; DeAngelis, A.; Koo, K.; Kranz, S.; Nastri, A.; Iseli, T.A.; Fua, T.; Wiesenfeld, D.
Abstract: Maxillary oral squamous cell carcinoma (OSCC) is uncommon. Surgical resection is challenging due to the anatomy, and the role of elective neck dissection (END) is not well-defined. A retrospective cohort study of patients with maxillary OSCC treated with primary surgery between 2007 and 2019 was conducted. Primary tumours of sinonasal origin with extension into the oral cavity were excluded. Survival analysis was performed using Kaplan–Meier and Cox proportional hazards models. Sixty-seven patients were included; mean follow-up was 55 months. On univariate analysis, clear (≥5 mm) margins were associated with higher disease-free (68% vs 36%, P  = 0.019) and overall survival (75% vs 36%, P  = 0.004) than close/involved (<5 mm) margins. In clinically node-negative patients, the risk of occult cervical metastasis in tumours with depth of invasion (DOI) ≥ 3 mm and T2–4 tumours was 22% and 25%, respectively. END in these groups was associated with a lower rate of loco-regional recurrence (DOI ≥3 mm subgroup: 5% vs 38%, P  = 0.029; T2–4 subgroup: 6% vs 50%, P  = 0.028) and longer time to recurrence (DOI ≥3 mm subgroup: 119 months vs 96 months, P  = 0.042; T2–4 subgroup: 117 months vs 56 months, P  = 0.031) than observation of the neck. On multivariate analysis, close/involved margins were associated with an increased risk of overall mortality (hazard ratio 3.4, 95% confidence interval 1.0–11.3, P  = 0.043) and disease recurrence (hazard ratio 2.8, 95% confidence interval 1.1–7.1, P  = 0.031). In maxillary OSCC, a ≥ 5 mm histological margin should remain the goal of ablative surgery. END should be considered in tumours with DOI ≥ 3 mm.